Cimory Dairyland Mini Zoo Sebagai Sarana Pendidikan Konservasi dan Interpretasi Lingkungan di SDN Kalibanteng Kidul 03 - Sa’diyah, Chalimatus; Nugraheni, Nursiwi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The article entitled "Cimory Dairyland Mini Zoo as a Means of Environmental Conservation and Interpretation Education at SDN Kalibanteng Kidul 03" generally aims to find out how Environmental Conservation and Interpretation Education is at SDN Kalibanteng Kidul 03. Based on the activities that have been carried out it can be shown that Environmental Conservation and Interpretation Education at SDN Kalibanteng Kidul 03 by conducting outing class activities to Cimory Dairyland Mini Zoo in Semarang Regency, outing class activities also seek to empower individuals with the skills and motivation necessary to take informed and responsible action to protect and preserve the environment. Conservation education is very important to increase public awareness and skills regarding forest and environmental conservation. This is done so that people have attitudes, actions and ways of thinking that are in accordance with efforts to preserve conservation areas, therefore how Conservation Education and Environmental Interpretation can be taught in an integrated manner from elementary schools.